Chronic bullous disease of childhood and linear IgA disease of adults are IgA1-mediated diseases. - Wojnarowska, F; Bhogal, B; Black, M (1994)
Linear IgA disease is characterized by the presence of linear IgA deposits at the basement membrane zone of the skin, and in some cases by circulating basement membrane zone antibodies. The disease occurs in both adults and children, and is designated adult linear IgA disease in the former and chronic bullous disease of childhood in the latter. The subclass distribution of the circulating and bound basement membrane zone antibodies was studied in 32 children and eight adults. The results were compared with five dermatitis herpetiformis patients and five normal controls. The circulating antibodies (39 patients) and the cutaneous deposits (39 patients) were IgA1 in all 40 patients with linear IgA disease. The cutaneous deposits in dermatitis herpetiformis were also all IgA1, and no circulating antibodies were detected. The controls were all negative. This large series of children and adults with linear IgA disease demonstrates that the circulating and cutaneous basement membrane zone deposits are all IgA1, and suggests that linear IgA disease is an IgA1-mediated disease.